Transparency – a patient-centric view on radiopharmaceutical extravasations - Kohl, Pam (Frontiers in Nuclear Medicine, 2023)
Most radiopharmaceuticals are intravenously administered during nuclear medicine imaging or therapy procedures. When a nuclear medicine clinician delivers some or all of a radioactive drug into a patient's healthy tissue rather than the vein as intended, a patient experiences an extravasation. Radiopharmaceutical extravasations provide zero patient benefit and considerable potential downsides, depending on the severity of the extravasations. What nuclear medicine patients want and need regarding the administration of radiopharmaceuticals is transparency. And yet in the year 2023, little transparency exists regarding these extravasations. From the patient perspective, transparency regarding extravasations is essential to improving care, ensuring radiation protection, reducing health inequities, and untangling the deeply disturbing and irregular relationship between the nuclear medicine community and their regulating body, The U.S. Nuclear Regulatory Commission. Transparency is also critical to help address many other questions regarding radiopharmaceutical extravasations.